(untitled) (Medicine Today, 2016)
This cross sectional study was carried out in the department of gastroenterology, Rangpur Medical College Hospital, Rangpur from January 2014 to July 2014 to compare between Invasive & Non-Invasive Diagnostic Evaluation of Tuberculosis Peritonitis In our prospective in clinically suspected patients. Total 30 patients (age 39.69±21.26, 18M/12F) with clinical suspicion of peritoneal tuberculosis were included in this study after analyzing selection criteria. Laparoscopic peritoneal biopsy with ’histopathological’ diagnosis was considered as gold standard against which accuracies non-invasive test of two biomarkers (ADA & CA-125) were compared. Cut off value of ADA and CA-125 is 24 U/l, 35 U/ml respectively. Sensitivity, specificity, positive predictive value, negative predictive value and accuracy of ADA as a diagnostic modality in peritoneal tuberculosis were 87.5%, 83.33%, 95.45%, 62.5% and 86.67% respectively whereas CA-125 was found to have 83.33% sensitivity, 50% specificity, 86.9% positive predictive value, 42.85% negative predictive value and 76.6% accuracy. Both biomarkers were simple, non-invasive, rapid and relatively cheap diagnostic test whereas laparoscopy was an invasive procedure, costly & requires trained staff and not without risk and also not feasible in the entire centre in our country. So ascitic fluid ADA and serum CA-125 was important non-invasive diagnostic test for peritoneal tuberculosis. Medicine Today 2015 Vol.27(2): 20-22